In vitro activities of cefoperazone and sulbactam singly and in combination against cefoperazone-resistant members of the family Enterobacteriaceae and nonfermenters. - Fass, R J (1990)
Among 28,000 isolates of the family Enterobacteriaceae and nonfermenters isolated at multiple medical centers, 1,084 (4%) were resistant to cefoperazone (MIC, greater than or equal to 64 micrograms/ml) and 1,711 (6%) exhibited cefoperazone MICs of 2 to 32 micrograms/ml. Ninety-six percent of these 2,795 isolates produced beta-lactamase, as determined by the nitrocefin test. Sulbactam alone (8 micrograms/ml) was inactive against 99.6% of the isolates other than Acinetobacter calcoaceticus and Pseudomonas cepacia. Sulbactam enhanced the activity of cefoperazone against 56% of the isolates of the family Enterobacteriaceae and 44% of the nonfermenters. In the presence of sulbactam concentrations of less than or equal to 8 micrograms/ml, 65% of the cefoperazone-resistant isolates had reductions in cefoperazone MICs of greater than or equal to 2 log2 dilution steps and were susceptible to less than or equal to 32 micrograms/ml. Antagonism was not observed.